Precise Point Positioning using GPS and compass observations - Li, Wei; Teunissen, Peter; Zhang, B.; Verhagen, S. (Springer Verlag, 2013)
The Compass Navigation Satellite system, which currently provides more than 12 satellites with three carrier signals, already satisfies the requirement of stand-alone positioning in the Asia–Pacific regional area. First an initial introduction and performance assessment of dual-frequency un-differenced precise point positioning (PPP) for GPS and Compass is presented, the results of which indicate that centimeter-level positioning accuracy of Compass-PPP is comparable to that of GPS-PPP. Then the combined GPS + Compass dual-frequency PPP model is introduced, followed by a numerical performance analysis and comparison with single GNSS-PPP. The results show that the combined GPS + Compass PPP can shorten the convergence time, but not necessarily improve positioning results by much if the satellites of the single GNSS system already have a good receiver-satellite geometry.